Short‐Term Morphology Relaxation of Thermoplastic Polyurethane Elastomers after Fast Strain Steps. Issue 9 (11th August 2020) - Stribeck, Almut; Schneider, Konrad; Eling, Berend; Pöselt, Elmar
Abstract: Strain steps are applied to elastomers in a pneumatic relaxometer and monitored by small‐angle X‐ray scattering (SAXS). The relaxometer provides a rise time of 13 ms for strain pulses of step height Δε = ±1 in strain. The basic character of the 2D SAXS frames is examined and corresponding invariants Q ( t ) are analyzed. Three thermoplastic polyurethanes (TPU) of hardness 85 Shore A with different soft segments are studied both unannealed and annealed. The first response of all materials is a fast morphology conversion which finishes within t mc  =250 ms. Because it has been untraceable, it is characterized by a settling stroke Q ( t mc ) − Q (0). The second response is a slow morphology adjustment process which complies with logarithmic relaxation. It is characterized by a relaxation rate D Q  = Q (10  t )/ Q ( t ) − 1. Comparison indicates that the nanoscopic morphology relaxation processes appear to have little direct relation to the macroscopic stress relaxation curves. The materials differ with respect to hard‐domain morphology stability and morphology recovery. Most unstable is the morphology of the annealed polyether‐based material. It forms nanofibrillary entities when strained. Abstract : How quickly and how strongly does the morphology of an elastomer react to strain steps? Tests with a fast pneumatic relaxometer on TPUs show a delayed, but then fast morphology conversion. This is followed by slow consolidation. In the chart, the height placement of the SAXS patterns indicates the scattering power.